LEXICAL DIVERSITY IN TEAM SPORTS: ENGLISH AND UZBEK LANGUAGE COMPARISON - Abdullayev Abdurashid of son Abdusattor (Western European Studies, 2024)
This article deals with borrowing vocabulary in the field of sports from English to Uzbek. It is established that in the Uzbek sports terminology there is a large number of anglicisms, which is explained by the development of appropriate technology for various sports in the English-speaking world. In the course of the study, a lexico-semantic analysis of Uzbek sports terms of English origin is carried out, and also the peculiarities of their word formation are revealed.
Keywords: sports terms; borrowing; anglicisms